2021
DOI: 10.3233/jad-201448
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypoxia Inducible Factor-1α in Alzheimer’s Disease

Abstract: Amyloid-β (Aβ) peptides and hyperphosphorylated tau protein are the most important pathological markers of Alzheimer’s disease (AD). Neuroinflammation and oxidative stress are also involved in the development and pathological mechanism of AD. Hypoxia inducible factor-1α (HIF-1α) is a transcriptional factor responsible for cellular and tissue adaption to low oxygen tension. Emerging evidence has revealed HIF-1α as a potential medicinal target for neurodegenerative diseases. On the one hand, HIF-1α increases AβP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 104 publications
0
20
0
Order By: Relevance
“…HIF-1α can enhance Aβ generation via promoting β/γ-secretases and inhibiting α secretase. Emerging evidence has also shown that HIF-1α could be a potential therapeutic target for neurodegenerative diseases [46]. Furthermore, HIF-1α has been reported to resist Aβ-derived neurotoxicity, inhibit tau hyperphosphorylation, and cause microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α can enhance Aβ generation via promoting β/γ-secretases and inhibiting α secretase. Emerging evidence has also shown that HIF-1α could be a potential therapeutic target for neurodegenerative diseases [46]. Furthermore, HIF-1α has been reported to resist Aβ-derived neurotoxicity, inhibit tau hyperphosphorylation, and cause microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 and SHH signaling pathways also show hyperactivities in the early stage of AD. Both pathways participate in Aβ accumulation and hyperphosphorylation of tau, thus contributing to AD pathogenesis ( Li et al, 2021 ; Wang Y. Y. et al, 2021 ). Interestingly, HIF-1 and SHH signaling pathways can both be activated by inflammatory signals ( Arumugam et al, 2011 ; McGettrick and O’Neill, 2020 ), and further promote pro-inflammatory phenotype transition of macrophages/microglia, forming a positive feedback loop to aggravate neuroinflammation ( Song et al, 2018 ; McGettrick and O’Neill, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HIF-1α is the core target in the initiation of the HIF-1 pathway. Wang YY et al ( Wang et al, 2021b ) revealed an intriguing finding that HIF-1 exerted both neuroprotective and negative effects. HIF-1α could enhance Aβ generation by promoting β/γ-secretases and inhibiting α-secretases, as well as inactivating microglia, to promote AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α could enhance Aβ generation by promoting β/γ-secretases and inhibiting α-secretases, as well as inactivating microglia, to promote AD pathogenesis. Although the role of HIF-1 signalling in the development of AD-related neurodegeneration is rather controversial ( Chai et al, 2014 ; Guo et al, 2017 ; Kim et al, 2017 ; Lu et al, 2018 ), increasing evidence has identified HIF-1α as a potential therapeutic target for AD ( Wang et al, 2021b ). Increased HIF-1 activity and/or increased expression of HIF-1 target proteins could alleviate cognitive impairment and AD progression by regulating glycolysis and capillary blood supply ( Iyalomhe et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%